Mauli Banana Stem Gel: A Potential Material for Dentin Remineralization Analyzed Using Fourier Transform Infrared Spectroscopy - Carabelly, Amy Nindia; Rahman, Yajma Kamiila; Puspitasati, Dewi; Erlita, Isyana; Wydiamala, Erida (Majalah Obat Tradisional, 2024)
Dental caries requires remineralizing agents to restore the dentin. Mauli banana stem gel is predicted to be an alternative material for mineral deposition during the remineralization process. Fourier transform infrared spectroscopy (FTIR) can analyze substances that indicate dentin remineralization. This study aimed to conduct an FTIR analysis of Mauli banana stem gel as a potential substitute material for dentin remineralization. The study utilized dentin slices obtained from the first premolars of the maxilla, which were demineralized using EDTA. Subsequently, the dentin slices were treated with CPP-ACP, 50% MBSG, 62,5% MBSG, and artificial saliva. A test tube containing 15 ml of artificial saliva was placed inside the smeared material, which was applied twice a day. It was left for three minutes and then rinsed with deionized water before being incubated at 37 °C. Basting was carried out for 21 days, and FTIR observations were performed. The major absorbance peaks detected were O-H and N-H stretch; C-H stretch; SCN stretch; Amide I; CO32-(v3) and collagen; Amide II; CH2 scissoring; C-H deformation; C-H stretching; Amide III; and PO43-(V3). MBSG demonstrated superior retention of dentin collagen compared to the control group, but it could not maintain the mineral content level on day 21. MBSG demonstrated a decrease in crystallinity due to a rise in carbonate content in the hydroxyapatite lattice. The study's findings indicate that MBSG remains unsuitable for dentin remineralization. Additional additives are necessary to enhance the levels of collagen and minerals in remineralized dentin.